2021
DOI: 10.1109/jsen.2021.3067841
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Interval Identification Using Interval Type-2 Fuzzy Logic Systems: Lake Water Level Prediction Using Remote Sensing Data

Abstract: This paper presents a novel approach to identify the prediction interval associated with data using interval type-2 fuzzy logic systems with support vector regression. For such a purpose, a constrained quadratic objective function is defined which is then solved using well-established quadratic programming approaches. Not only does the output of interval type-2 fuzzy logic system replicates the measured value, but also it provides the lower bound and the upper bound for measured data values. In the proposed ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…At time T, the candidate cell state 𝐢 Μƒ is defined as: π‘ͺ ̃𝒕 = 𝒕𝒂𝒏𝒉(𝑾 π‘ͺ β‹… [𝒉 π’•βˆ’πŸ , 𝒙 𝒕 ] + 𝒃 π‘ͺ ) (15) At time T, the current cell state 𝐢 𝑑 is defined as: π‘ͺ 𝒕 = 𝒇 𝒕 * π‘ͺ π’•βˆ’πŸ + 𝑰 𝒕 * π‘ͺ ̃𝒕 (16) The output gate 𝑄 𝑑 outputs the current time step's state information and determines the value of the next hidden state:…”
Section: Long Short-term Memory (Lstm)mentioning
confidence: 99%
See 1 more Smart Citation
“…At time T, the candidate cell state 𝐢 Μƒ is defined as: π‘ͺ ̃𝒕 = 𝒕𝒂𝒏𝒉(𝑾 π‘ͺ β‹… [𝒉 π’•βˆ’πŸ , 𝒙 𝒕 ] + 𝒃 π‘ͺ ) (15) At time T, the current cell state 𝐢 𝑑 is defined as: π‘ͺ 𝒕 = 𝒇 𝒕 * π‘ͺ π’•βˆ’πŸ + 𝑰 𝒕 * π‘ͺ ̃𝒕 (16) The output gate 𝑄 𝑑 outputs the current time step's state information and determines the value of the next hidden state:…”
Section: Long Short-term Memory (Lstm)mentioning
confidence: 99%
“…Experimental results indicated that the ensemble model exhibited better prediction accuracy and applicability than individual models. Khanesar et al [15] employed interval type 2 fuzzy logic systems with support vector regression to identify the prediction interval associated with data. In the proposed approach, a penalty term was added to the cost functions to exert full control over the width of the prediction interval.…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of this method is lower than the enhanced Karnik-Mendel and higher than other approximate models of Biglarbegian-Melek-Mendel [24] and Nie-Tan [25,26]. The computational complexity for the Maclaurin-based first-order approximator is less than the EKM model, as it does not necessitate the sorting procedure required by EKM [27,28]. The Maclaurin-series-expansion-based first-order approximate output of the IT2FLS is as follows [27,28]:…”
Section: Interval Type-2 Fuzzy Systems Structurementioning
confidence: 99%
“…The computational complexity for the Maclaurin-based first-order approximator is less than the EKM model, as it does not necessitate the sorting procedure required by EKM [27,28]. The Maclaurin-series-expansion-based first-order approximate output of the IT2FLS is as follows [27,28]:…”
Section: Interval Type-2 Fuzzy Systems Structurementioning
confidence: 99%
“…The first 80% of the generated data is used for training and the last 20% is chosen for testing purposes. The comparison results with several other methods including Type-1 TSK FNS [27], Type-2 TSK FNS [27], Feedorward Type-2 FNN [11], SIT2FNN [28], SEIT2 FNN [29], TSCIT2FNN [30], IT2 FNN-GD [26], IT2 FNN-SMC [26], IT2 FNNPSO+ SMC [26], IT2 IFLS -DEKF+GD [11], and IT2FLS with Modified SVR [31] are presented in Table 1,where results support the idea that the proposed approach is effective at system identification by outperforming the other tested algorithms. The behavior of the proposed identification system for the training and tesing data is presented in Figures 3 and 4, respectively.…”
Section: Benchmark Identification Problemmentioning
confidence: 99%